Consumption of energy drinks is associated with depression, anxiety, and stress in young adult males: Evidence from a longitudinal cohort study. Issue 11 (26th August 2020) - Kaur, Simrat; Christian, Hayley; Cooper, Matthew N.; Francis, Jacinta; Allen, Karina; Trapp, Gina
Abstract: Background: Energy drinks (EDs) claim to boost mental performance, however, few studies have examined the prospective effects of EDs on mental health. This study examined longitudinal associations between ED use and mental health symptoms in young adults aged 20 years over a 2‐year period. Methods: Data were drawn from Gen2 (Generation 2) of the Raine Study, a prospective population‐based study in Western Australia. Self‐report questionnaires assessed ED consumption and mental health symptoms (Depression Anxiety Stress Scale [DASS]‐21) when Gen2 participants were 20 and 22 years old. Changes in ED use and DASS‐21 scores over time were analyzed and results presented for the whole sample and by sex. Results: For the whole sample ( n  = 429), participants who changed from being a non‐ED user to an ED user had an average increase in stress scores of 2.30 (95% confidence interval [CI] = 0.04, 4.55) across the 2‐year follow‐up. Males, but not females who changed from being a non‐ED user to an ED user had an average increase in depression, anxiety, and stress scores of 6.09 (95% CI = 3.36, 8.81), 3.76 (95% CI = 1.82, 5.70), and 3.22 (95% CI = 0.47, 5.97), respectively. Conclusion: ED consumption may be a possible marker for mental health symptoms in young male adults. Practicing clinicians could consider screening for ED use in routine assessments of mental health, particularly for young males presenting with depression, anxiety, and stress symptoms.